Joseph Conrad and the remembrance of things past : remembering, writing, and narrative - Yao, Xiaoling (2019)
This dissertation aims to explore the ways in which Joseph Conrad’s autobiographical memory and writing cross-fertilize each other in Almayer’s Folly (1895), Heart of Darkness (1902), and The Shadow-Line (1917). By studying how Conrad repeatedly returns to and continuously reworks his past moments through the use of different stylistic and narrative strategies in these works, I challenge the idea that narrative is a transparent mirror of received experiences. Instead, the author’s lived past is transformed into a remembered one that warps, rewrites, or illuminates his initial experience. As such, I argue that Conrad’s continuous writerly engagement with his past registers, and progressively dramatizes, the complexity of personal remembering. More specifically, this dissertation begins by investigating Conrad’s initial engagement with memory and writing in Almayer’s Folly, primarily proposing the presence of unconquerable memory, and the idea of writing as a means to remember a lost past. The discussions of Heart of Darkness highlight the writer’s increasingly complex understanding of the remembering process by focusing on the narrative’s inability to recapture the original past, and remembering as an essentially interpretative act. Its examination of Conrad’s verbal rendering of personal experience culminates in exploring The Shadow-Line, a text where the narration of past events and the present act of writing are conflated. Ultimately, it foregrounds the polyphonic interactions between experience and expression, as well as the porous boundaries between fact and fiction.